Drivers of plant functional group richness and beta diversity in fire-dependent pine savannas - Freeman, Johanna E.; Kobziar, Leda N.; Leone, Erin H.; Williges, Kent (Diversity & distributions, 2019)
Aim To assess the drivers of plant functional group richness and beta diversity in fire‐maintained North American Coastal Plain (NACP) savannas. Location The southern portion of the NACP, a global biodiversity hotspot. This region is characterized by fire‐dependent pine savanna fragments that are isolated within a matrix of agriculture, urban development, non‐pyrogenic plant communities and plantation forestry. Methods We used nested quadrats to sample plant species on 30 fire‐maintained savanna preserves in Florida and Georgia, USA. We analysed between‐site Sørenson dissimilarity, a measure of beta diversity, using NMDS and PerMANOVA. We measured nestedness using NODF, and we used Betapart to partition Sørenson dissimilarity into nestedness and turnover components. We used linear and generalized linear mixed models to explore drivers of functional group richness and composition, including fire regime (return interval, number of fires, time since fire and seasonality), vegetation structure (herbaceous cover, woody cover and tree density) and spatial factors (surrounding landscape and geographic distance). Results We found turnover‐dominated beta‐diversity patterns in all functional groups. Turnover was explained partly by spatial and environmental gradients, but roughly half of the turnover between sites was unexplained. Species richness was higher on sites where fire and fire surrogates had been used longer and more consistently, and these effects were partly independent of current vegetation structure. Fire regimes containing more growing season fire and more diversity of burn seasons promoted higher species richness. Relationships between small‐scale and large‐scale species richness varied by soil type and functional group. Main conclusions Fire‐maintained savannas in the southeastern NACP vary greatly in their plant functional group richness, but high beta diversity resulting primarily from species turnover suggests that even species‐poor sites can harbour less‐common members of the regional plant metacommunity. Prescribed fire regimes that include growing season fire as well as a diversity of burn seasons may best promote species and functional group richness.